2014
DOI: 10.1002/bies.201400151
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of eukaryotic cells from the perspective of peroxisomes

Abstract: Beta-oxidation of fatty acids and detoxification of reactive oxygen species are generally accepted as being fundamental functions of peroxisomes. Additionally, these pathways might have been the driving force favoring the selection of this compartment during eukaryotic evolution. Here we performed phylogenetic analyses of enzymes involved in beta-oxidation of fatty acids in Bacteria, Eukaryota, and Archaea. These imply an alpha-proteobacterial origin for three out of four enzymes. By integrating the enzymes' h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 67 publications
(98 reference statements)
0
23
0
1
Order By: Relevance
“…These structures are small, membrane-enclosed organelles, discovered by Christian De Duve (De Duve, 1969) that employ enzymes involved in a variety of energetic and metabolic reactions (Speijer (2011) BioEssays 33:88; Bolte et al (2015) BioEssays 37:195; Moore (2015) BioEssays 37:113). De Duve hypothesized that peroxisomes originated due to endoplasmic reticulum (ER) stress caused by rising levels of oxygen in the environment (Berner et al, 2000).…”
Section: Physical Phenomena and Cellular Requirementsmentioning
confidence: 99%
“…These structures are small, membrane-enclosed organelles, discovered by Christian De Duve (De Duve, 1969) that employ enzymes involved in a variety of energetic and metabolic reactions (Speijer (2011) BioEssays 33:88; Bolte et al (2015) BioEssays 37:195; Moore (2015) BioEssays 37:113). De Duve hypothesized that peroxisomes originated due to endoplasmic reticulum (ER) stress caused by rising levels of oxygen in the environment (Berner et al, 2000).…”
Section: Physical Phenomena and Cellular Requirementsmentioning
confidence: 99%
“…This bypasses the respiratory chain, leading to loss of ATP generation from FADH 2 oxidation and H 2 O 2 formation. Interestingly, it was recently found that all peroxisomal enzymes involved (two enzymes, as steps 2 and 3 are catalysed by a single bifunctional enzyme after gene fusion), of course apart from the peroxisomal acyl-CoA oxidase used in step 1, are derived from mitochondria [41]. Though ‘peroxisomes’ now have accreted many extra functions (differing per species and tissue), comparative analysis shows β-oxidation to be their most ancient pathway [27,41].…”
Section: Peroxisomesmentioning
confidence: 99%
“…Interestingly, it was recently found that all peroxisomal enzymes involved (two enzymes, as steps 2 and 3 are catalysed by a single bifunctional enzyme after gene fusion), of course apart from the peroxisomal acyl-CoA oxidase used in step 1, are derived from mitochondria [41]. Though ‘peroxisomes’ now have accreted many extra functions (differing per species and tissue), comparative analysis shows β-oxidation to be their most ancient pathway [27,41]. More complicated pathways are presumed to have been relocated in eukaryotes, maybe following positive selection of low levels of proteins ending up in aberrant cellular environments [42].…”
Section: Peroxisomesmentioning
confidence: 99%
“…The peroxisomal b-oxidation pathway plays an indispensable role in the catabolism of fatty acids in animals, fungi and plants (Bolte et al, 2015). In addition, in plants and animals, b-oxidation in peroxisomes is involved in the metabolism of a number of other specialized compounds (Poirier et al, 2006).…”
Section: Introductionmentioning
confidence: 99%